An Initial Membership Profile of the Financial Therapy Association - Kristy L Archuleta; Anita K Dale; Dan Danford; Kelley Williams; Erika Rasure; Emily Burr; Kurt Schindler; Brett Coffman (Journal of Financial Therapy, 2011)
The Financial Therapy Association (FTA) was established in 2010 to bring practitioners and researchers together to develop tools and techniques to address emotional, behavioral, relational, cognitive, and economic aspects of financial health. Ultimately, those interested in the new field of financial therapy are most interested in answering the following key questions: Why do people do what they do with money and how can practitioners better help their clients deal with the complexities of the volatile economy that places tremendous stress on individuals and families? Financial therapy is emerging as a unique field that links scholars, practitioners, and mental health professionals in ways that consider these and other important questions. FTA is especially unique because of its diverse and accomplished membership, which includes mental health and financial professionals, educators, and researchers. The purpose of this “Profile” is to highlight how experienced and established professionals from both the mental health and finance domains have joined together to build a new profession, and to provide benchmark information regarding how the practice of financial therapy is occurring in the United States and other countries.
Keywords: financial therapy